Enigma [videorecording (DVD)] - Apted, Michael; Scott, Dougray, 1965-; Winslet, Kate; Northam, Jeremy, 1961-; Harris, Robert, 1957- (Columbia TriStar Home Entertainment, 2002)
Still reeling from the disappearance of his lover, a brilliant code-breaker is summoned to Blechley Park, Britain's top-secret intelligence campus. Now he must face his toughest assignment--crack the Nazis' infamous Enigma codes. Putting together the pieces of a puzzle, he discovers the link between his lovers' disappearance, U-boats closing in on Allied cargo ships and a mass grave in Poland.